2020
DOI: 10.1016/j.heliyon.2020.e03373
|View full text |Cite
|
Sign up to set email alerts
|

A case of spontaneous heterotopic pregnancy in natural conception complicated with hemoperitoneum

Abstract: A B S T R A C THeterotopic pregnancy, defined as simultaneous intrauterine and ectopic gestations, is an uncommon occurrence in women who conceive without assisted reproduction techniques. We present the case of 28 years old female with strong family history of multiple gestations, who presented with acute severe abdominal pain and diagnosed with spontaneous heterotopic pregnancy in natural conception. Ectopic pregnancy was successfully removed surgically to conserve the uterine pregnancy. After one week, pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 9 publications
(15 reference statements)
0
14
0
8
Order By: Relevance
“…Our review revealed improved outcomes for intrauterine pregnancies when the extrauterine ones were located in the fallopian tubes, as compared to the interstitial ectopic sack [26]. Almost all articles included in our study reported an unaffected intrauterine pregnancy, with the exception of one article that reported a spontaneous abortion [38]. However, the literature describes an unaffected intrauterine pregnancy in two thirds of cases and spontaneous abortion in one third [32].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Our review revealed improved outcomes for intrauterine pregnancies when the extrauterine ones were located in the fallopian tubes, as compared to the interstitial ectopic sack [26]. Almost all articles included in our study reported an unaffected intrauterine pregnancy, with the exception of one article that reported a spontaneous abortion [38]. However, the literature describes an unaffected intrauterine pregnancy in two thirds of cases and spontaneous abortion in one third [32].…”
Section: Discussionmentioning
confidence: 60%
“…Although the presence of extrauterine pregnancy is usually associated with risk factors, we found a number of case reports that presented patients with heterotopic pregnancies in the absence of known risk factors [4,19,26,27,29,33,34,36]. Five articles mentioned the existence of risk factors for the patients, such as a history of pelvic inflammatory disease, history of repeated miscarriages and intrauterine interventions, history of abdominal surgery [18,23,30,38,39], thus emphasizing the importance of identifying patients with risk factors and performing differential diagnosis on individuals with clinical signs of SHP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of heterotopic pregnancy is estimated at 1/30.00, above 1/100 when associated with in vitro fertilization, and 1/900 when using clomiphene citrate [4] . The important risk factors for the development of a heterotopic pregnancy include family history, endometriosis, tubal disease, history of pelvic inflammation, high hormone levels, embryo transfer technique [5] .…”
Section: Discussionmentioning
confidence: 99%
“…Heterotropic pregnancy is relatively uncommon in spontaneous conception with 1 in 30,000 cases reported, the incidence of heterotopic pregnancy increases to 1 in 3900 when conception is enhanced with various assisted reproduction techniques (ART) including in vitro fertilization, super ovulation, and intrauterine insemination. 2 The incidence of heterotropic pregnancy could be rising, especially with advent of ART and use of clomiphene citrate for ovulation induction. 4,8 Also reported is effect of pelvic inflammatory disease on ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 99%